Draft Annual Plan Tamil Nadu 2007-08 State Planning Commission - Planning Commission (Planning Commission, 2007)
Over the ten five year plans implemented since Independence Tamil Nadu has demonstrated a strong record of all-round development. It has been a trail-blazer in ensuring social justice and inclusiveness, and this emphasis on economic and social equity has resulted in sustained improvements in the living conditions of all sections of society. The challenge for Tamil Nadu in the Eleventh Plan is to give a further impetus to inclusiveness and equity, while achieving a high rate of growth. The state has a relatively a modem economy compared to other states. The state is undergoing a structural transformation. The services sector grew at the rate of 8.73 % during the 10th plan period with 56.04% share in the State Gross Domestic Product (GSDP) in 2004-05. The contribution of the agricultural sector, dwindled as a share of State Gross Domestic Product from 23.78 % in the 1994-95 to 13.28 % in 2004-05. The industry sector roughly maintained its share in the economy.
Draft Annual Plan Tamil Nadu 2007-08
Government of Tamil Nadu